2016
DOI: 10.1080/17436753.2016.1236533
|View full text |Cite
|
Sign up to set email alerts
|

Alumina/copper foams produced by replica using a double impregnation process

Abstract: Rheological behaviour of Al 2 O 3 and CuO suspensions was characterised in order to fabricate Al 2 O 3 /Cu foams as an alternative way to produce foams with better mechanical properties than common Al 2 O 3 foams. Different quantities of raw materials were combined to select the formulations for the ceramic-metal foams. Foams were produced by a double impregnation process, followed by a thermal cycle and a reduction cycle. In this work, materials were characterised trough zeta potential, SEM and optical dilato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Considering the temperature effect during the synthesis process (Miranda Hernández et al, 2018), it was found that the calcium aluminate material synthesized by an in-situ solid state reaction between Al 2 O 3 and CaCO 3 obtained from snail shells is feasible, but the results show that this material is brittle. However, there are several investigations showing that the incorporation of metallic or ceramic particles into the matrix of the ceramic materials modified their physical properties and mechanical properties, such as hardness, fracture toughness, elastic modulus, and fatigue strength (Naga et al, 2019;Tahaa et al, 2017;Granados et al, 2017;José et al, 2016;Sergejev and Antonov, 2006;Moradkhani et al, 2013;Pramanick, 2015;González-Morán et al, 2017;Shukla et al, 2010;Dapievea et al, 2018). In other works, the effect of silver particles with calcium aluminate was studied and it was found that with silver particles, calcium aluminate has favorable conditions as an endodontic sealer, that presents improved antibiofilm properties with a positive effect on antimicrobial behavior (Almeida et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the temperature effect during the synthesis process (Miranda Hernández et al, 2018), it was found that the calcium aluminate material synthesized by an in-situ solid state reaction between Al 2 O 3 and CaCO 3 obtained from snail shells is feasible, but the results show that this material is brittle. However, there are several investigations showing that the incorporation of metallic or ceramic particles into the matrix of the ceramic materials modified their physical properties and mechanical properties, such as hardness, fracture toughness, elastic modulus, and fatigue strength (Naga et al, 2019;Tahaa et al, 2017;Granados et al, 2017;José et al, 2016;Sergejev and Antonov, 2006;Moradkhani et al, 2013;Pramanick, 2015;González-Morán et al, 2017;Shukla et al, 2010;Dapievea et al, 2018). In other works, the effect of silver particles with calcium aluminate was studied and it was found that with silver particles, calcium aluminate has favorable conditions as an endodontic sealer, that presents improved antibiofilm properties with a positive effect on antimicrobial behavior (Almeida et al, 2018).…”
Section: Introductionmentioning
confidence: 99%